2014
DOI: 10.17219/acem/37127
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Right and Left Ventricular Diastolic Functions with Tissue Doppler Echocardiography in Congestive Heart Failure Patients with Coexisting Acute Pulmonary Embolism

Abstract: Background. acute pulmonary embolism (aPe), despite improvements in diagnostic methods, often remains undiagnosed. Recently, systolic dysfunction has also been described as assessed by new echocardiographic techniques, such as tissue Doppler imaging (TDI). Objectives. In our study we have attempted to assess diastolic function within the mitral and tricuspid annuli in congestive heart failure (cHf) patients with coexisting aPe. Material and Methods. The study included 39 patients with cHf with sinus rhythm, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Some studies have noted a parallel decrease in both systolic and diastolic RV function [14,15]. At the same time, it was shown that RV diastolic dysfunction can be detected with preserved systolic function in patients with diabetes [16], in patients with congestive heart failure and pulmonary embolism [17].…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have noted a parallel decrease in both systolic and diastolic RV function [14,15]. At the same time, it was shown that RV diastolic dysfunction can be detected with preserved systolic function in patients with diabetes [16], in patients with congestive heart failure and pulmonary embolism [17].…”
Section: Discussionmentioning
confidence: 97%
“…We focused on the RV diastolic function since its development precedes systolic dysfunction both in experiment 26 , 27 and during the disease’s development 10 , 28 , adversely affecting the prognosis at the same time 7 , 29 . Our study confirmed the influence of the above factors on the presence of RVDD.…”
Section: Discussionmentioning
confidence: 99%
“…Chest radiographs may show an enlarged cardiac silhouette, edema at the bases of the lungs, and vascular congestion, all signs of congestive heart failure. On chest radiographs, Kerley B lines can be detected in florid heart failure [11,12]. Unscheduled short-term readmission may be avoided with proper assessment of heart filling pressures and appropriate prognostication.…”
Section: Introductionmentioning
confidence: 99%